Influence of the English Language on Librarianship Terminology on Polish University Sites - Dąbrowska, Izabela; Cyran, Katarzyna (2022)
The following article discusses theoretical and practical aspects concerning terminology in the field of librarianshipby showing how new terms are coined or incorporated from other languages. It presents key librarian terminologyused on the websites of leading Polish academic libraries aiming to assess the extent of the influence of the Englishlanguage on the Polish librarianship jargon. The analysis draws on fundamental terms selected from five websitesand discusses their etymology. Three main trends – neologisms, borrowings and semanticisms – are shown andillustrated with appropriate examples.
Keywords: LIS terminology; librarianship; specialist terms; neologisms; borrowings; semanticisms